1999
DOI: 10.1046/j.1469-8137.1999.00503.x
|View full text |Cite
|
Sign up to set email alerts
|

Juncus bulbosus as a pioneer species in acidic lignite mining lakes: interactions, mechanism and survival strategies

Abstract: Bulbous rush (Juncus bulbosus) initiates plant colonization in extremely acid lakes resulting from coal mining operations. Various analytical techniques (methylene blue\agar method, Ti$ + -citrate solution) X-ray diffraction (XRD), scanning electron microscopy (SEM), and Energy-dispersive X-ray (EDX) were used to assess the mechanisms and strategies employed by J. bulbosus to overcome the extreme conditions. The plant releases oxygen into the rhizosphere in turn increasing the redox potential and induci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 29 publications
2
30
0
1
Order By: Relevance
“…These results differ from others (Chen et al 2006;Batty et al 2000;Greipsson 1994Greipsson , 1995Liu et al 2004b) but agree with our conclusions (Liu et al 2007) and those of Liu et al (2005) who also found that root tissue was the main barrier to As uptake by rice plants when arsenite was supplied. Similar results were also reported for metal uptake by other wetland plants, for example Pb and Cd uptake by Typha latifolia (Ye et al 1998), Cu, Zn and Pb uptake by water hyacinth (Vesk et al 1999), and Fe, Mn, Cu and Zn uptake by Juncus bulbosus (Chabbi 1999). The increase in Fe nutritional level in plants may partially alleviate the potential toxic effects of Cd to plant growth, as shown by the decreased Cd concentrations in roots and shoots at Fe50 than at Fe0 in both experiments (Fig.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results differ from others (Chen et al 2006;Batty et al 2000;Greipsson 1994Greipsson , 1995Liu et al 2004b) but agree with our conclusions (Liu et al 2007) and those of Liu et al (2005) who also found that root tissue was the main barrier to As uptake by rice plants when arsenite was supplied. Similar results were also reported for metal uptake by other wetland plants, for example Pb and Cd uptake by Typha latifolia (Ye et al 1998), Cu, Zn and Pb uptake by water hyacinth (Vesk et al 1999), and Fe, Mn, Cu and Zn uptake by Juncus bulbosus (Chabbi 1999). The increase in Fe nutritional level in plants may partially alleviate the potential toxic effects of Cd to plant growth, as shown by the decreased Cd concentrations in roots and shoots at Fe50 than at Fe0 in both experiments (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…The formation of iron plaque on the root surfaces of rice and other wetland plants is due to the release of oxygen and oxidants in the rhizosphere and the subsequent oxidation of ferrous to ferric iron and the precipitation of iron oxide or hydroxide on the root surface (Armstrong 1967;Chen et al 1980b;Taylor et al 1984). Mineralogical investigations in wetland fields have shown that the composition of iron plaque in Phalaris arundinacea is mainly ferrihydrite (∼63%) with smaller amounts of goethite (32%) and minor amounts of siderite (5%; Hansel et al 2001), or predominately goethite in Juncus bulbosus (Chabbi 1999) and rice (Chen et al 1980a). Iron plaque therefore has chemical properties similar to those of iron oxides in the soil and can thus sequester both cations and anions and alter the uptake and accumulation of elements by plants.…”
Section: Introductionmentioning
confidence: 99%
“…These plant species differ in nitrogen nutrition, extent of radial oxygen loss, and lifestyle, presumably resulting in differential, plant species-specific effects on rhizosphere-and root-associated AOA and AOB communities. L. uniflora prefers nitrate as the nitrogen source, while J. bulbosus prefers ammonium (41,45); oxygen release is high to moderate from the roots of L. uniflora and J. bulbosus (9,12) but is minor from the roots of M. alterniflorum (M. Herrmann, P. Stief, and A. Schramm, unpublished results); L. uniflora and J. bulbosus remain photosynthetically active throughout the year, while only the below-ground parts of M. alterniflorum are retained during winter.…”
mentioning
confidence: 99%
“…are known to be a representative acidic soil indicator, 35) and this genus can adapt to acidic soil conditions with several acid-tolerant strategies, including bacterial plaque on the rhizoplane. 36) In a similar manner, functional rhizobacteria might be involved in the surviving strategy of the wild Juncus community in the acidic soil paddocks of South Kalimantan.…”
Section: Discussionmentioning
confidence: 99%